Study of Octupole States in 150Sm and 158Gd Nuclei Within Sdf-Interacting Boson Model (Sdf-IBM-1) Framework - A. Hashim, Tuqa; N. Abood, Saad (Al-Nahrain Journal of Science, 2025)
The collective octupole states found in 150,152Sm and 148,150Gd isotopes are explained inside the structure of the sdf-interacting boson model-1 (sdf-IBM1). The specifications of the IBM Hamiltonian are fitted with the experimental energy levels. By diagonalizing the IBM Hamiltonian, For positive as well as negative parity states, excitation energies and electric transition rates can be obtained. We then compare these resulting spectroscopic features with the currently available experimental data. Furthermore, the framework of excited 0+ states is investigated along with its relationship to double octupole phonons. The sdf-IBM-1 model demonstrates a high level of accuracy in portraying the observed trends in low-energy quadrupole states.